The Influence Of Organizational Fairness, Work-Life Balance, And Job Satisfaction On Organizational Commitment - Neila Afivaturokhmah (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2025)
The rapid development of business competition and workforce dynamics in the industrial era requires organizations to strengthen employee commitment as a key factor in achieving sustainability. Organizational commitment is closely related to employees' perceptions of fairness, balance between work and personal life, and job satisfaction. This study aims to analyze the influence of organizational justice, work-life balance, and job satisfaction on organizational commitment among employees of CV. Media Grafika Yogyakarta. The research employed a quantitative approach with a census method involving 45 employees as respondents. Data were collected using a structured questionnaire and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS version 3. The results reveal that organizational justice and work-life balance do not have a significant effect on organizational commitment, while job satisfaction has a positive and significant effect. Simultaneously, the three independent variables have a positive effect on organizational commitment, with an R-square value of 0.561, indicating that 56.1 percent of the variance in organizational commitment is explained by these factors.